2007
DOI: 10.1016/j.jss.2006.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Natural Killer Cell Lysis in Breast Cancer Patients with High Levels of Psychological Stress is Associated with Altered Expression of Killer Immunoglobin-Like Receptors

Abstract: Background-We previously reported that cancer-related psychological stress is associated with reduced natural killer (NK) cell lysis. We hypothesized that reduced NK cell cytotoxicity in patients with increased levels of stress would correlate with alterations in the expression of inhibitory NK cell receptors (killer immunoglobulin-like receptors, or KIRs). The specific aim of this study was to examine KIR expression in patients with high or low levels of psychologic stress and correlate alterations in KIR exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 45 publications
0
32
0
2
Order By: Relevance
“…132 Although psychological stress in female breast cancer patients impairs NK cell activity, it does not alter lymphokine-activated killer activity. 133 Similarly, in the Nurses' Health Study, the relative breast cancer risks were the same for women reporting passive jobs and those reporting high-strain jobs. 134 The connection between the duration of shift work and the increased risk of breast cancer needs to be fully explored, as increased breast cancer risk has been noted in those working shifts for just half a year as well as in those working for >30 years.…”
Section: Shift Work and Cancermentioning
confidence: 93%
“…132 Although psychological stress in female breast cancer patients impairs NK cell activity, it does not alter lymphokine-activated killer activity. 133 Similarly, in the Nurses' Health Study, the relative breast cancer risks were the same for women reporting passive jobs and those reporting high-strain jobs. 134 The connection between the duration of shift work and the increased risk of breast cancer needs to be fully explored, as increased breast cancer risk has been noted in those working shifts for just half a year as well as in those working for >30 years.…”
Section: Shift Work and Cancermentioning
confidence: 93%
“…In individuals with stage II and III breast cancer before a surgery intervention, high stress levels as assessed with a self-reported questionnaire (i.e., Impact of Event Scale) predicted subsequent reduced lysis potential by natural killer (NK) cells, as well as diminished response of NK cells to IFN gamma and decreased proliferative response of peripheral blood lymphocytes to a monoclonal antibody stimulating the T-cell receptor 118 . A subsequent small follow-up study involving a subset of patients demonstrated that dysfunctional alterations in NK-cells activity in association with high levels of psychological stress may be long-lasting, although the relevance of stress-induced detrimental effects on cancer survival and recurrence is still unclear 119 .…”
Section: Stress As a Modulator Of Immune Response In Depression And Cmentioning
confidence: 99%
“…Both surgical and psychological stress are known to affect negatively a number of immune parameters (1)(2)(3)(4)(5)(6)(7). Surgical stress evokes a potent local and systemic inflammatory response with transient increases in proinflammatory cytokines interleukin (IL)-1␤, IL-6, IL-8, and tumor necrosis factor (TNF)-␣ (2), as well as a generalized state of immunodepression (1,3,4).…”
Section: Introductionmentioning
confidence: 99%